A fuzzy method for the usability evaluation of nuclear medical equipment - Cláudio Henrique dos Santos Grecco; Isaac José Antonio Luquetti dos Santos; Marcos Santana Farias; Larissa Pereira de Farias; Alfredo Marques Vianna Filho (Brazilian Journal of Radiation Sciences)
To avoid errors when handling nuclear medical equipment, it is important to develop products with a high degree of usability. This can be achieved by performing usability evaluations in the product development process to detect and mitigate potential usability problems. Usability evaluation focuses on how well users can learn and use a product to achieve their goals. To gather information about usability, practitioners use a variety of methods that gather feedback from users about an existing interface or plans related to a new interface. A wide range of usability evaluation methods have been proposed, but few methods focus on developing an objective and practical evaluation method for usability. Moreover, the usability evaluations are based on human judgments and most methods cannot fully solve the subjectivity of these evaluations. In order to remedy this deficiency, the purpose of this work is to adopt a Fuzzy Set Theory (FST) approach to establish a method for the usability evaluation of nuclear medical equipment based on usability heuristics for user interface design and international standards for ergonomics of human-system interaction. To exemplify the method we performed a usability evaluating of the Digital Spectrometer ESP 13004 by testing it with representative users. The results showed that the method is a proactive tool to provide a basis for checking usability of medical device interfaces.